E-176 Elevated serum S100B predicts adverse clinical outcome and DWI abnormalities in acute subarachnoid hemorrhage patients. (22nd July 2018) - Kayan, Y; Almandoz, J Delgado; Fease, J; Wallace, A; Scholz, J; Milner, A; Banerji, N; Mulder, M
Abstract : Purpose: To determine the correlation of serum S100B protein levels with clinical outcome and the presence of DWI abnormalities in acute subarachnoid hemorrhage (SAH). Methods: Patients with diffuse SAH at our institution were offered enrollment in a prospective study in which serial MRI, including DWI, FLAIR, PWI, and ASL sequences, was performed at admission, 7 days, 30 days, and upon the development of signs/symptoms of vasospasm. As well, serum S100B levels were measured at the time of each MRI. Patient demographics, Hunt-Hess grade, modified Fisher score, and underlying lesion and treatment technique were recorded. Poor clinical outcome was defined as mRS 3–6 at discharge. Mean S100B levels were compared using Student's t-test. ROC analyses were performed using MedCalc v18.2.1. p<0.05 was considered statistically significant. Results: Between November 2013 and August 2017, 50 patients were enrolled, 37 women, mean age 58, 20 current smokers. Hunt-Hess grade mean was 3.0. Modified Fisher score mean was 3.5. All underlying vascular lesions were treated endovascularly: 17 ACA aneurysms, 14 ICA aneurysms (including PCOM), 10 MCA aneurysms, 3 basilar tip aneurysms, 1 vertebral aneurysm, 1 posterior fossa AVM, and 4 angiographically-negative SAHs. Mean serum S100B was 73.4 ng/L, 55.1 ng/L and 57.8 ng/L on admission, at 7 days and 30 days, respectively. Overall, serum S100B was significantly higher on admission than at 7 days (p=0.01). Admission serum S100B was significantly higher in patients with poor outcome at discharge (p=0.0003) and in patients with any DWI abnormalities on admission (p=0.0004). The correlation of elevated serum S100B with the presence of DWI abnormalities persisted at 7 days (60.7 ng/L versus 42.8 ng/L, p=0.007). ROC analyses revealed a cutoff of admission S100B>69 ng/L resulting in a sensitivity of 54.8% and a specificity of 94.7% for poor outcome at discharge with an AUC of 0.74 (95% CI 0.60–0.85, p=0.0005), and a cutoff of admission S100B>61 ng/L resulting in a sensitivity of 64.5% and a specificity of 82.4% for the presence of any DWI abnormalities on admission with an AUC of 0.75 (95% CI 0.61–0.86, p=0.0004). Conclusion: Admission S100B levels were elevated in setting of acute subarachnoid hemorrhage. Higher S100B levels were associated with poor outcomes at discharge and the presence of DWI abnormalities, both on admission and at 7 days. Disclosures: Y. Kayan: 2; C; Medtronic, Penumbra. J. Delgado Almandoz: 2; C; Medtronic, MicroVention, Penumbra. J. Fease: None. A. Wallace: None. J. Scholz: None. A. Milner: None. N. Banerji: None. M. Mulder: None.